Thinking punk. (1st June 2016) - Ryde, Robin; Bestley, Russ
In the double issue special edition of Punk & Post Punk, 4.2/4.3, Russ Bestley wrote a provocative article entitled '(I want some) demystification: Deconstructing punk', reflecting on punk scholarship and the tropes and stereotypes that may be narrowing discourse on the subculture. In one section of the essay, the author questioned the value of a number of books on punk as a lifestyle and philosophy, including Craig O'Hara's The Philosophy of Punk: More Than Noise! (1999), Lars J. Kristiansen's Screaming For Change: Articulating a Unifying Philosophy of Punk Rock (2012) and Robin Ryde's The Truth of Revolution, Brother: The Philosophies of Punk (2014) (Bestley 2015: 119). Robin Ryde reached out to challenge some of the points raised in the original article and exercise a right to reply. This led to an extended dialogue between the two authors, which we have decided to reproduce in edited form here, along with a 'think piece' essay by Ryde reflecting on a range of contemporary attitudes towards punk and questioning where our subculture might be heading.